Microbiome diversity and variations in industrial hemp genotypes - Waqar Ahmad; Lauryn Coffman; Ram L. Ray; Venkatesh Balan; Aruna Weerasooriya; Abdul Latif Khan (Scientific Reports)
Abstract Microbes like bacteria and fungi are crucial for host plant growth and development. However, environmental factors and host genotypes can influence microbiome composition and diversity in plants such as industrial hemp (Cannabis sativa L.). Herein, we evaluated the endophytic and rhizosphere microbial communities of two cannabidiol (CBD; Sweet Sensi and Cherry Wine) and two fibers (American Victory and Unknown). The four hemp varieties showed significant variations in microbiome diversity. The roots had significantly abundant fungal and bacterial endophyte diversity indices, whereas the stem had higher fungal than bacterial diversity. Interestingly, the soil system showed no significant diversity variation across CBD vs. fiber genotypes. In fungal phyla, Ascomycota and Basidiomycota were significantly more abundant in roots and stems than leaves in CBD-rich genotypes compared to fiber-rich genotypes. The highly abundant bacterial phyla were Proteobacteria, Acidobacteria, and Actinobacteria. We found 16 and 11 core-microbiome bacterial and fungal species across genotypes. Sphingomonas, Pseudomonas, and Bacillus were the core bacteria of fiber genotypes with high abundance compared to CBD genotypes. Contrarily, Microbacterium, and Rhizobium were significantly higher in CBD than fiber. The Alternaria and Gibberella formed a core-fungal microbiome of fiber-genotype than CBD. Contrarily, Penicillium, and Nigrospora were significantly more abundant in CBD than fiber genotypes. In conclusion, specific hemp genotypes recruit specialized microbial communities in the rhizosphere and phyllosphere. Utilizing the core-microbiome species can help to maintain and improve the growth of hemp plants and to target specialized traits of the genotype.